Concomitant versus Delayed Cholecystectomy in Bariatric Surgery - Hatem Elgohary; Mahmoud El Azawy; Mohey Elbanna; Hossam Elhossainy; Wael Omar (Journal of Obesity)
Background. Obesity and weight loss after bariatric surgery have a close association with gallbladder disease. The performance and proper timing of laparoscopic cholecystectomy (LC) with bariatric surgery remain a clinical question. Objective. Evaluation of the outcome of LC during bariatric surgery whether done concomitantly or delayed according to the level of intraoperative difficulty. Methods. The prospective study included patients with morbid obesity between December 2018 and December 2019 with preoperatively detected gallbladder stones. According to the level of difficulty, patients were allocated into 2 groups: group 1 included patients who underwent concomitant LC during bariatric surgery, and group 2 included patients who underwent delayed LC after 2 months. In group 1, patients were further divided into subgroups: LC either at the beginning (subgroup A) or after bariatric surgery (subgroup B). Results. Operative time in group 1 vs. 2 was 92.63 ± 28.25 vs. 68.33 ± 17.49 (p<0.001), and in subgroup A vs. B, it was 84.19 ± 19.62 vs. 130.0 ± 31.62 (p<0.001). One patient in each group (2.6% and 8.3%) had obstructive jaundice, p>0.001. In group 2, 33% of asymptomatic patients became symptomatic for biliary colic p>0.001. LC difficulty score was 2.11 ± 0.70 vs. 5.66 ± 0.98 in groups 1 and 2, respectively, p<0.001. LC difficulty score decreased in group 2 from 5.66 ± 0.98 to 2.26 ± 0.78 after 2 months of bariatric surgery, p<0.001. Conclusion. Timing for LC during bariatric surgery is challenging and should be optimized for each patient as scheduling difficult LC to be performed after 2 months may be an option.